Intersex Stigma and Discrimination: Effects on Patient-Centred Care and Medical Communication - Charron, Marilou; Saulnier, Katie; Palmour, Nicole; Gallois, Hortense; Joly, Yann (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Individuals with intersex variations fall outside the normative sex binary of male and female for various reasons. These individuals are highly stigmatized and discriminated against in the legal, medical and social spheres. In this paper, we analyze manifestations of such discrimination in the healthcare context and hypothesize that Patient Centred Care (PCC) and Shared Decision Making (SDM) approaches are improperly practiced with intersex individuals. Through a narrative review of current literature, we present evidence of improper practice of PCC and SDM and its effects on intersex individuals and, in the pediatric context, their parents. Misinformation by medical practitioners to parents of intersex individuals promotes the perpetuation of unnecessary surgical interventions. We propose strategies to improve intersex medical care, including better adherence to SDM and PCC guidelines as well as the sociocultural normalisation of intersex identity. Current perceptions of surgical interventions done on intersex infants and children need to better align with evidence-based physical and psychological health risks. All these strategies are part of preserving the autonomy and physical integrity of intersex individuals and ensuring that their well-being remains at the heart of their care in the medical context.